A high capacity bentonite clay for the sorption of aflatoxins. Issue 2 (1st February 2020) - Wang, Meichen; Hearon, Sara E.; Phillips, Timothy D.
ABSTRACT: Previously a calcium bentonite clay (CB) has been shown to tightly bind aflatoxins in vitro, significantly reduce mortality and morbidity in animals, and decrease molecular biomarkers of aflatoxin exposure in humans and animals. Extensive studies have shown that CB is safe for human and animal consumption. In further work, we have investigated a highly active sodium bentonite (SB) clay (SB-E) with enhanced aflatoxin sorption efficacy compared to CB and other clays. Computational models and isothermal analyses were used to characterise toxin/clay surface interactions, predict mechanisms of toxin sorption, and gain insight into: 1) surface capacities and affinities, and 2) thermodynamics and sites of toxin/surface interactions. We have also used a toxin-sensitive living organism ( Hydra vulgaris ) to confirm the safety and predict the efficacy of SB-E against aflatoxin toxicity. Compared to CB, SB-E had a higher capacity for aflatoxin B1 (AfB1 ) at pH 2 and 6.5. Results from this work suggest that high capacity clays such as SB-E can be used as effective aflatoxin enterosorbents to decrease short-term exposures in humans and animals when included in food and/or water during extended droughts and outbreaks of aflatoxicosis. Graphical Abstract: